Prevalence and associated factors of myopia in high-school students in Beijing - Wu, Li-Juan; Jonas, Jost B. (PLOS ONE, 2015)
Purpose: To evaluate prevalence and associated factors for myopia in high school students in Beijing. Methods: Grade 10 and 11 high school students were randomly selected from nine randomly selected districts of Beijing. The students underwent non-cylcoplegic auto-refractometry and an interview. Results: Out of 4798 eligible students, 4677 (93.4%) students (mean age:16.9±0.7years;range:16-18 years) participated. Mean refractive error of right eyes and left eyes was −2.78±2.29 diopters and −2.59±2.50 diopters, respectively. Prevalence of myopia (defined as ≤ −1.00 diopters in the worse eye) was 80.7% (95% Confidence Interval (CI): 79.6-81.8%). Out of 3773 students with myopia, 1525 (40.4%) wore glasses daily. In multiple logistic regression analysis, a higher prevalence of myopia was associated with female sex (odds ratio (OR) = 1.31;95%CI:1.11-1.55), Han ethnicity (OR = 1.64;95%CI:1.28-2.11), attending key schools (OR = 1.48;95%CI:1.24,1.77), higher family income (OR = 1.37;95%CI:1.09-1.71), longer time spent for near work (OR = 1.43;95%CI:1.06-1.93), shorter near work distance (OR = 1.87;95%CI:1.55-2.26), lower frequency of active rest during studying (OR = 1.40;95%CI:1.16-1.70), and parental myopia (OR = 2.28;95%CI:1.80-2.87). The interaction between distance from near work and time spent for near work was statistically (P = 0.03) significant. In multiple logistic regression analysis, higher prevalence of high myopia (≤-6.0 diopters) was associated with studying in key schools (OR = 1.38;95%CI:1.05,1.81), lower frequency of active rest during studying (OR = 1.40;95%CI:1.09,1.79), and a higher number of myopic parents (OR = 2.66;95%CI:2.08,3.40). Conclusions: A prevalence of about 80% for myopia and a prevalence of about 10% for high myopia in students aged 16 to 18 years and attending classes of grade 10 and 11 in a Chinese metropolitan region is another example of the high prevalence of moderate and high myopia in metropolitan areas of China. With this young myopic generation getting older, myopia as cause for visual impairment and blindness may further increase in importance. Future studies may address whether active rests during studying with looking into the distance are preventive against myopia development or progression.